Dimethyl Sulfoxide Mixed-Solvent Engineering for Efficient Perovskite/Silicon Tandem Solar Cell - Haifeng Zhang; Youling He; Qian Li; Hao Zhang; Yinqing Sun; Tengteng Yang; Yinyi Ma; Tian Yang; Xindi Zheng; Lin Mao (Energies)
The integration of perovskite with silicon for constructing tandem solar cells (TSCs) represents a promising route in photovoltaic technology. The hybrid sequential deposition (HSD) method, combining thermal evaporation and spin-coating, is crucial for developing perovskite films in textured perovskite/silicon tandem solar cells. However, the process faces challenges due to incomplete reactions caused by the dense perovskite coverage layer (CPCL) formed from high-crystallinity precursors. The CPCL hinders the diffusion of organic salts into the bottom precursor layer, leading to performance degradation and accelerated device aging. Herein, this study explores several polar solvents as additives to n-butanol (nBA) solvent in order to enhance the permeability of organic salts through the CPCL, and we demonstrate that dimethyl sulfoxide (DMSO) as an additive solvent can effectively assist organic salts in rapidly diffusing through the precursor layer, thereby promoting the complete transformation of uniform perovskite crystals. The resulting perovskite films exhibited complete conversion, uniform crystallization, and improved quality. As a result, the target TSCs achieved an increased maximum power conversion efficiency (PCE) of 29.12%. This study offers a robust pathway for depositing high-quality perovskite films on industrial-grade textured silicon substrates, laying a solid foundation for advancing perovskite/silicon tandem solar cells technology.